Influences of InGaN quantum well thickness on the internal quantum efficiency for GaN LED visible Light communication - Lee, Mei Yee; Mat Jubadi, Wasuzarina (Penerbit UTHM, 2020)
Nowadays, semiconductor lighting industry has been developed rapidly throughout the world. Light emitting diodes (LEDs) are known as a compound semiconductor device that can emit visible light when there is an electron current passed through it. In recent years, the group III – nitride semiconductor compounds with gallium (Ga) have developed as the leading materials for manufacturing energy-efficient LED [1]. The reason of GaN becoming the trend is due to the excellent optical properties and it is able to emit a wide range of wavelengths in the visible spectrum at the efficiency which greater than traditional lighting technologies [2]. The group III – nitride semiconductor compounds are typically grown with wurtzite crystal structure which consists of a large band gap around 1.0 eV to 6.0 eV.